«Արարատ» ամսագրի պատմագիտական նշանակութիւնը - Էդիկ Մինասյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассмотрена роль первого на Кавказе арменоведческого журнала «Арарат» основанного в 1868 году в Вагаршапате, который в течении 50 лет издавал статьи в области арменоведения и историографии. The article shows the role of ”Ararat”, the first Armenological journal in the Caucasus founded in 1868 in Vagharshapat, which within 50 years published articles on Armenological and historiographical issues, dealing with all the historical periods of Armenia.
Keywords: History; Periodicals